The effects of plyometric training on sprint performance: A meta-analysis - de Villarreal, E. S.; Requena, B.; Cronin, J. B. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this meta-analysis was to attempt to gain a clear picture of the magnitude of sprint performance improvements expected after chronic plyometric training (PT) and to identify specific factors that influence the treatment effects. Studies employing a PT intervention and containing data necessary to calculate effect size (ES) were included in the analysis. A total of 26 studies with a total of 56 ES met the inclusion criterion. Analysis of ES demonstrated that the strategies that seem to maximize the probability of obtaining significantly (p < 0.05) greater improvement in sprint performance included training volume for <10 weeks; a minimum of 15 sessions; and high-intensity programs with >80 combined jumps per session. To optimize sprint enhancement, the combination of different types of plyometrics and the use of training programs that incorporate greater horizontal acceleration (i.e., sprint-specific plyometric exercises, jumps with horizontal displacement) would be recommended, rather than using only one form of jump training (p < 0.05). No extra benefits were found to be gained from doing plyometrics with added weight. The loading parameters identified in this analysis should be considered by the professional sprinters and specialized trainers with regard to the most appropriate dose-response trends PT to optimized sprint performance gains.